Incidence of intracranial haemorrhage in low-birth weight infants and its outcome: a hospital based prospective study - Debbarma, Rajesh; De, Asim; Debbarma, Sanjib (International Journal of Research in Medical Sciences, 2016)
Background: Intracranial haemorrhage (ICH) is one of the most important neurological complications in low birth weight (LBW) infants, especially in very low birth weight (VLBW) infants during the neonatal period. The objectives of the present study was to determine the incidence of intracranial hemorrhage among the low birth weight infants (<2.5kg), to determine the outcome of intracranial hemorrhage among the low birth weight infants (<2.5 kg) and to establish the relationship between the birth weight and degree of intracranial hemorrhage. Methods: It is a prospective observational study. The study was conducted from November 2011- April 2013 in the neonatal unit, Department of pediatrics medicine in collaboration with Department of radio diagnosis in Agartala, Government Medical College and GBP Hospital, Agartala, India. Results: Out of 400 infants, 32 (8%) of infants were ≤1 kg and 177 (44.25%) were 2-2.5 kg. Infants who had normal delivery 213 (53.25%) and 37 (9.25%) had difficult in vaginal delivery. Incidence of ICH among low birth weight newborns was 29%.Incidence of intra-ventricular hemorrhage (IVH) among low birth weight newborns detected in the study was 19.5% (79 out of 400). Among different types of intracranial hemorrhage IVH comprises the larger part (68.1%). Regarding various grading (severity) of IVH, found the study were, grade I IVH 35.4%, grade II IVH-41.7%,grade III IVH- 16.4% and grade IV IVH -6.3%. There was a direct association between birth weight and ICH and significant (p=03) association was found especially in babies below 1 kg. Overall mortality rate among newborn following various types of ICH was found to be 22.4%. Regarding long outcome of attending follow up clinic for 10 months showed delayed developmental milestone 13%, 8.6% develop seizure disorder and 13% develop hydrocephalus and 21.7% develop early sign cerebral palsy. Conclusions: Low gestational age, specially <34 weeks, very low birth weight, male gender, difficult vaginal delivery, birth asphyxia, and hypothermia are risk factors for intracranial hemorrhage, specially intra-ventricular hemorrhage. For better evaluation of risk factors for ICH and its outcome, multicentric study should be performed with large number of simple and longer time period of follow up with the help of newer modalities of investigation.